TEKNIK MENYEMBUNYIKAN PESAN RAHASIA MENGGUNAKAN STEGANOGRAPHY DAN CRYPTOGRAPHY - Amin, M. Miftakul (Jurnal Informatika, 2015)
Development of Internet technology has demonstrated the communication that occurs does not require face to face directly. Safety factor becomes an important issue in the communication using the Internet network. Various attempts were made to keep the information security and confidentiality can be maintained. Steganography and cryptography techniques present as a technique to achieve data security. This research attempts to develop an application that can be used for communication by using two techniques. In this study steganography method used is the Least Significant Bit (LSB) whereas cryptography method used is the Caesar cipher. From the research that has been done can be generated an application that has been able to perform encryption and decryption of secret messages that can be hidden in a digital image color (24 bit). Key words : steganography, cryptography, LSB